Effect of Different Concentrations of Vermicompost (Biohumus) On the Root Collar Diameter and Height Growth in the Seedlings of Anatolian Black Pine - Atik, Atilla (Journal of Forests, 2014)
In the present study, effect of vermicompost, a product of Biohumus®, on the root collar diameter and height growth of 1+0 aged seedlings of Anatolian black pine growing in Bartin-Turkey was investigated. Seedlings were treated with three different concentrations of vermicompost solution from seed dibbling. Statistical comparison of morphologic data for treatments was performed using ANOVA test while the treatments were categorised using Duncan test. Compared to control, mean root collar diameter growth was found to be about 25% higher in seedlings in V1 treatment type (Vermicompost of 1:1000) and nearly 26% more in V2 and V3 treatment type while height growth was 13% more in V1 treatment and 20% in V2 and V3 treatment. Findings of the study were thought that Vermicompost can be used to obtain quality black pine seedlings in nurseries by developing root collar and plant height.